Determination of ramipril in human plasma and its fragmentation by UPLC-Q-TOF-MS with positive electrospray ionization - Szpot Paweł; Buszewicz Grzegorz (Acta Pharmaceutica)
This report presents the application of ultra-performance liquid chromatography coupled to quadrupole time-of-flight mass spectrometry with positive electrospray ionization, to determine ramipril in human plasma. First, the proteins in human plasma were precipitated using acetonitrile, then the supernatant was extracted by ethyl acetate at pH 3 and finally, the extract was analyzed using a UPLC-QTOF- MS system. The method was validated and the coefficient of determination (R2) was > 0.999, the lower limit of quantification (LLOQ) was 0.5 ng mL-1. Precision, recovery and stability were determined for three different concentrations of ramipril. RSD for this method ranged from 3.3 to 8.6 %. The intra-day mean recovery was from 65.3 to 97.3 %. In addition, the fragmentation of ramipril was studied. Due to high resolution of the spectrometer, it was possible to measure fragment masses accurately and determine their molecular and chemical formulas with high accuracy.